Evaluation of the Effectiveness of Internal Control Practice in the Ethiopia’s Public Universities - Hussien, Abdella (African Journal of Leadership and Development, 2022)
In recent times there are a shift from an emphasis on just the presence of internal control to also on the effectiveness of internal controls practice. The main objectives of this study were to evaluate the effectiveness of the internal control practices in selected Ethiopia Public Universities. Semi-structured questions were designed based on standards 17 principles of the internal control framework model of the Committee of Sponsoring Organizations of the Treadway Commission (COSO), five elements of internal controls: control environment, risk assessment, control activities, information and communication, and monitoring. Primary data was collected from five purposively selected public universities and a total of 100 of their respective administrative and academic employees were used as the study unit. And furthermore, qualitative information from interviews was supplemented with a survey questionnaire the data. The data were analyzed using descriptive statistics and multiple regression analysis methods. The result is presented in statistics such as mean, standard deviation, frequency, and percentages. Over all finding of the study reveals that the Effectiveness of Internal control practice is positively and highly correlated with all Elements of the internal control system. Moreover, the result shows, Higher education institutions (HEIs) managing bodies are less than average in proactively responding to changing aspects of HEIs fraud risks, respondents believe HEIs are weak in IT securities control and less effective public university board of directors oversight functions. Thus, the study recommended that the HEIs needs more effective implementation and strengthening the implementation and monitoring of its policies and procedures and establishing risk early –warning and proactive risk assessment to improve its internal control system.